STUDY OF SUSTAINABILITY IN MANAGEMENT OF MALABAR BLOOD SNAPPER FISHERIES IN THE INDIAN OCEAN COASTAL WATERS, SUMBAWA REGENCY - Randi, Evron Asrial, L.A.T.T.W. Sukmaring Kalih, Rusmin Nuryadin (Indonesian Journal of Aquaculture and Fisheries (IJAF), 2020)
Coastal waters in the south of Sumbawa Island as a habitat for coral reef ecosystem in a potential habitat for the life of reef fish resources. One of them is red snapper or Malabar snapper or Malabar blood snapper (Lutjanus malabaricus Schneider, 1801) which contributes to increasing the value of Indonesia's exports. The problem of Malabar blood snapper fisheries management is population degradation and over exploited. This study aims to estimate the sustainability status of fisheries management of Malabar blood snapper in the coastal waters of the Indian Ocean. Data compilation was carried out during the period June-July 2019 in Cemplung Beach, Labangka, Sumbawa Regency. The sustainability analysis of the of Malabar blood snapper fisheries management applies the technique of Rapreefish (Rapid Appraisal for Reef Fisheries) which was modified and developed from Rapfish (Rapid Appraisal for Fisheries). Sustainability studies were carried out on the biological dimension (11 attributes) as an output factor, and the technology dimension (16 attributes) as an input factor. Management of Malabar blood snapper fisheries involving fishermen and collector?s trader has been carried out conventionally. The result is the level of utilization and exploitation of the Malabar blood snapper resources each overfishing and over exploitation. While the biological dimension, the management status is "Quite Sustainable", and the technology dimension is "Less Sustainable". Improving the management's sustainability status requires intervention from strategic stakeholders. The purpose is toincrease the size of the captured Malabar blood snapper and catching it in potential fishing grounds.